Fit & Strong! Promotes Physical Activity and Well-Being in Older Cancer Survivors - Reynolds, Jana; Thibodeaux, Lorie; Jiang, Luohua; Francis, Kevin; Hochhalter, Angie (Frontiers in Public Health, 2015)
.